Nazifying Christian Theology: Walter Grundmann and the Institute for the Study and Eradication of Jewish Influence on German Church Life - Heschel, Susannah (Church history, 1994)
The Third Reich's Kirchenkampf (church struggle) is sometimes mistakenly understood as referring to the Protestant churches' resistance to National Socialism. In fact, the term refers to an internal dispute between members of the Bekennende Kirche [Confessing Church (hereafter BK)] and members of the Deutsche Christen [German Christians (hereafter DC)] over control of the Protestant church. While not all members of the BK opposed Hitler's policies, the movement called for an autonomy of the church from National Socialist legal measures, particularly the racial laws, motivated both by theological and political considerations. The DC, by contrast, sought to introduce National Socialist policies and ideology into the church, especially Nazi racial laws, and modify church doctrine in accord with National Socialist ideology. Yet the antisemitism at the heart of the DC has been either ignored or marginalized by most historians. Indeed, some historians have incorrectly suggested that the DC underwent a dissolution at the end of 1933, from which it never recovered, or have presented the DC as a political creation of National Socialism, ignoring its theological roots.